ANALISIS ISI BAHAN AJAR BAHASA INDONESIA KELAS IV DALAM MENINGKATKAN LITERASI MEMBACA SISWA SEKOLAH DASAR - Adellia Nur Aini, Niken Kumala Sari, Selvi Andari, Elda Rintan Parwati, Hermawan Wahyu Setiadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the content of Indonesian language teaching materials for fourth-grade elementary school students in the context of developing student reading literacy. Reading literacy is a basic competency that includes the ability to understand, interpret, evaluate, and reflect on the meaning of texts, and is an important foundation for lifelong learning. In the Independent Curriculum, reading literacy learning emphasizes the integration of cognitive, affective, and socio-cultural aspects through meaningful and contextual reading activities. This study used a descriptive qualitative approach with a content analysis method for the Indonesian Language Student Book for Fourth-grade Elementary Schools under the Independent Curriculum (Kemendikbudristek, 2022). Data were collected through text inventory, literacy activity categorization, character value analysis, and interpretation of the book's content context. The analysis results show that the teaching materials accommodate various types of texts, such as narrative, descriptive, and expository, and integrate reading aloud, guided, and reflective activities. The book structure is arranged thematically and contextually with character values ​​that support the formation of a Pancasila student profile. However, critical literacy still needs to be strengthened to enable students to analyze and evaluate reading content more deeply. Thus, fourth-grade Indonesian language teaching materials can be said to contribute positively to improving basic reading literacy, but they require text enrichment and reflective strategies that encourage students' critical thinking skills. Keywords: Content Analysis, Teaching Materials, Indonesian, Reading Literacy, Elementary School